Relationship between complaints presented by emergency patients and the final outcome - Helisamara Mota Guedes; Kesia Meiriele Souza; Patrícia de Oliveira Lima; José Carlos Amado Martins; Tânia Couto Machado Chianca (Universidade de São Paulo, 2015)
AbstractObjective: to relate complaints presented by emergency room patients, classified using the Manchester Triage System, with the final outcome (discharge/death/transfer).Methods: prospective cohort study, involving 509 patients who were admitted to the emergency room and remained there for more than 24 hours after admission, being monitored to the final outcome. Data were analyzed with a statistical program using descriptive and analytical statistics.Results: the mean age of the patients was 59.1 years and 59.3% were male. The main complaints were unwell adult (130 - 22.5%), shortness of breath in adults (81 - 14.0%), abdominal pain in adults (58 - 10.0%) and behaving strangely (34 - 5.9%), with 87% of the patients being discharged. More deaths were found in the patients classified in the severe colors, with 42.8% classified as red, 17.0% as orange and 8.9% as yellow. Among the patients classified as green, 9.6% died.Conclusion: in the various colors of the Manchester Triage System, death prevailed in patients that presented the complaints of unwell adult, shortness of breath, head injury, major trauma, diarrhea and vomiting. The higher the clinical priority the greater the prevalence of death.